2020
DOI: 10.1002/ange.202008757
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching Effects of Tetrazines and Their Diels–Alder Products: Mechanistic Insight Toward Fluorogenic Efficiency

Abstract: Inverse electron demand Diels-Alder reactions between s-tetrazines and strained dienophiles have numerous applications in fluorescent labeling of biomolecules.H erein, we investigate the effect of the dienophile on the fluorescence enhancement obtained upon reaction with at etrazine-quenched fluorophore and study the possible mechanisms of fluorescence quenching by both the tetrazine and its reaction products.T he dihydropyridazine obtained from reaction with astrained cyclooctene shows aresidual fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…While the fluorescence intensity of the former was similar to that of 1 , the intensity was more than 2‐fold stronger for the latter. These results were consistent with those reported by Buccella et al., who found that the dihydropyridazine unit could suppress the fluorescence emission of several fluorophores through PET [33] . In contrast, only one major peak at 35.23 min was observed in the chromatogram of the mixture of 1 and BCN‐CH 2 OH, which was due to the corresponding pyridazine (Figures S2b and 3a).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While the fluorescence intensity of the former was similar to that of 1 , the intensity was more than 2‐fold stronger for the latter. These results were consistent with those reported by Buccella et al., who found that the dihydropyridazine unit could suppress the fluorescence emission of several fluorophores through PET [33] . In contrast, only one major peak at 35.23 min was observed in the chromatogram of the mixture of 1 and BCN‐CH 2 OH, which was due to the corresponding pyridazine (Figures S2b and 3a).…”
Section: Resultssupporting
confidence: 92%
“…These results indicate that the aromatization of 1,4‐dihydropyridazines to pyridazines is strongly dependent on the substituent of TCO. It has been reported that 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ) can be used to promote the aromatization of 1,4‐dihydropyridazines [33, 35] . However, the addition of DDQ is undesirable in biological systems.…”
Section: Resultsmentioning
confidence: 99%
“…The first example of turn‐on FL−Tzs (fluorescence enhancement: 15–20 folds) based on Tz−TCO click reaction was reported by Weissleder and coworkers by utilizing FRET mechanism [32] . Futher study showed that the fluorescence intensity of BODIPY FL−Tz conjugate with FRET effect was enhanced about 24 times after reaction with TCO [75] . Actually, to achieve higher imaging contrast, FL−Tzs with higher turn‐on folds (>100) of fluorescence after reaction with TCO structure are preferred for bioimaging applications [76] .…”
Section: Recent Advances Of Imaging Probes Based On the Tz−tco Click ...mentioning
confidence: 99%
“…Amongst fluorogenic probes, tetrazine modulated fluorophores are remarkable examples due to the 2‐in‐1 feature of the tetrazine moiety, such as being the quencher of fluorescence and the bioorthogonal handle at the same time [11, 12] . Indeed, we and others have demonstrated that tetrazines efficiently quench [13] the fluorescence of various blue/green excitable cores, e.g., coumarins and BODIPYs, via energy (e.g., FRET, [14, 15] TBET [10, 11] ) or electron transfer (PET [10] ) processes. Direct conjugation of tetrazines [16, 17] to a fluorescent frame may also result in a dark lowest lying excited state.…”
Section: Introductionmentioning
confidence: 97%